1973
DOI: 10.1037/h0034784
|View full text |Cite
|
Sign up to set email alerts
|

Power to the powerless: Locus of control and the use of power.

Abstract: Internally and externally controlled subjects were given a range of powers with which to supervise three fictitious workers, one of whom presented a supervisory problem. It was found that in dealing with the problem worker, externally controlled subjects (high powerless) used significantly more coercive power (e.g., threat of deduction of points, threat of firing) than did internally controlled subjects (low powerless). In addition, internals relied more on personal persuasive powers than did externals. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
4

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 12 publications
5
47
0
4
Order By: Relevance
“…This implies that external entrepreneurs would be more inclined to pursue low-cost strategies in dynamic environments. Being involved in this personality-environment congruency situation, external entrepreneurs are likely to exert more coercive power over their employees to ensure that all the requirements are met to produce against low costs (Goodstadt & Hjelle, 1973). Consistently, earlier studies revealed that externals conduct more conservative behavior particularly when confronted with high-risk situations (Baron, 1968).…”
Section: Low-cost Strategiesmentioning
confidence: 86%
See 1 more Smart Citation
“…This implies that external entrepreneurs would be more inclined to pursue low-cost strategies in dynamic environments. Being involved in this personality-environment congruency situation, external entrepreneurs are likely to exert more coercive power over their employees to ensure that all the requirements are met to produce against low costs (Goodstadt & Hjelle, 1973). Consistently, earlier studies revealed that externals conduct more conservative behavior particularly when confronted with high-risk situations (Baron, 1968).…”
Section: Low-cost Strategiesmentioning
confidence: 86%
“…This can, for instance, be achieved through maintaining strict cost control systems, enforcing cost reductions, and prescribing tight specifications for materials to be used in the production process. As externals are better suited to deal with relatively routine-like and clearly structured tasks (Rotter, 1966;Spector, 1982), and because they tend to conduct a leadership style that relies on coercion (Abdel-Halim, 1981;Goodstadt & Hjelle, 1973;Mitchell, Smyser, & Weed, 1975), the aptitudes of external entrepreneurs tend to align with the tasks needed to pursue a low-cost strategy Govindarajan, 1989;Rotter, 1966;Spector, 1982) -much more so than their internal counterparts (see above).…”
Section: Low-cost Strategiesmentioning
confidence: 96%
“…Importantly, numerous studies document relationships between locus of control, behavior, and performance (Anderson, Hellriegel, & Slocum, 1977;Goodstadt & Hjelle, 1973;Kinicki & Vecchio, 1994;Mitchell, Smyser, & Weed, 1975;Perlow & Latham, 1993;Storms & Spector, 1987). Despite the apparent relationship between locus of causality and locus of control, we are aware of only one study that investigates the relationship between these two variables.…”
Section: Locus Of Controlmentioning
confidence: 95%
“…A leader's vision typically reflects enduring life themes (Zaleznick & Kets de Vries, 1985). Moreover, childhood experiences of powerlessness are associated with using coercive influence techniques (Goodstadt & Hjelle, 1973). Abused children often distance themselves from others and compartmentalize (or disassociate) painful issues (Cramer, 2000;Vaillant, 1977).…”
Section: Negative Life Themesmentioning
confidence: 98%